Do state visits affect cross-border mergers and acquisitions? - Aleksanyan, Mark; Hao, Zhiwei; Vagenas-Nanos, Evangelos; Verwijmeren, Patrick (Journal of Corporate Finance, 2021)
This paper studies the relation between state visits and cross-border merger and acquisition (M&A) activity. Based on 1161 state visits and 11,531 cross-border acquisitions, we find that corporations from visiting countries are more likely to acquire corporations in countries hosting the visit. Domestic acquisitions in the host country or M&As with non-visiting countries are not elevated. Evidence from instrumental variable analysis points towards a causal effect of state visits on M&A activity. Further analysis shows that the elevated M&A activity originating from visiting countries can be attributed to business networking and a reduction in investment uncertainty and cultural barriers.